Update on the Value of Lung Ultrasound Examination in Acute Decompensated Heart Failure Patients with Various Left Ventricular Ejection Fraction - Hui Zhang; Yunlong Zhu; Na Li; Jianping Zeng (Reviews in Cardiovascular Medicine, 2022)
Acute decompensated heart failure (ADHF) is one of the most common causes of hospital admission for cardiovascular diseases. ADHF often affects the elderly population, is associated with high morbidity, admission rate and mortality. Pulmonary congestion (PC) is the most common cause of hospitalization among ADHF patients. Previous studies have shown that lung ultrasound (LUS) serves as a valuable tool for the evaluation of PC in patients with heart failure in terms of diagnosis, guiding of the treatment, and post-discharge monitoring. The use of LUS for ADHF is well described and already widely used in the daily clinical practice. PC might differ in ADHF patients with different left ventricular ejection fraction value and treatment options should be steadily adjusted according to the LUS-derived PC results to improve the outcome. This review summarized the value of LUS examination in patients with ADHF with preserved, mildly reduced, and reduced left ventricular ejection fraction, aiming to expand the rational use of LUS, promote the LUS-guided management and improve the outcome among patients with ADHF.